Characterization and formulation of miswak film for the treatment of chronic periodontitis: An in vitro study - Santhosh Sekar; Siji Jacob; Thanga Kumaran Suthanthiran; Syed Dhasthaheer; Swathigan Vikraman; Kanimozhi Kaliappan (Wolters Kluwer Medknow Publications, 2020)
Introduction: Miswak is a tooth brushing stick that contains many ingredients that are beneficial for maintenance of oral hygiene. The aim of this study is to formulating a film containing miswak extract for treatment of chronic periodontitis. Materials and Methods: Here we tested the miswak raw extract invitro against Porphyromonas gingivalis and Herpes simplex virus-1 (HSV-1). The film was prepared using solvent casting method. Disintegration test was conducted to find the stability of the film. Results: Cytotoxicity of miswak was also tested. Minimum inhibitory concentration against P. gingivalis was 62.5 µg/mL. Therapuetic index against HSV-1 was 11.3 µg/mL. Cytotoxicity against 50% Vero cells was present at 210 µg/mL. Based on this invitro study 100 µg/mL dose was calculated to be incorporated in a film of size 0.5 mm × 0.4 mm. This film is made of polymers HPMC K 100 and Eudragit L 100. Disintegration test of the film showed that they remained stable for around 5 days. Conclusion: In the present study we formulated the miswak raw extract containing film that can act against P. gingivalis and HSV-1. So it can be used to treat chronic periodontitis by placing it in periodontal pockets.